2022
DOI: 10.3389/fnut.2022.1016592
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency increases the risk of bacterial vaginosis during pregnancy: Evidence from a meta-analysis based on observational studies

Abstract: BackgroundBacterial vaginosis (BV) is the most common microbiological syndrome in women of childbearing age, causing numerous adverse health issues in pregnant women. Several observational studies have discussed the association between vitamin D deficiency and the risk of BV during pregnancy, but the results were inconclusive. Therefore, this meta-analysis aimed to explore the association between vitamin D deficiency and BV risk in pregnant women.Materials and methodsWe searched four databases, including PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Following deduplication, 673 meta-analyses remained, which underwent title and abstract screening with 123 meta-analyses selected for full-text screening. Finally, 16 meta-analyses met the inclusion criteria for this umbrella review [15][16][17][18][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following deduplication, 673 meta-analyses remained, which underwent title and abstract screening with 123 meta-analyses selected for full-text screening. Finally, 16 meta-analyses met the inclusion criteria for this umbrella review [15][16][17][18][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Search Resultsmentioning
confidence: 99%
“…For maternal outcomes, a low level of vitamin D ( < 50 nmol/L), significantly increased the risk of preterm birth (OR = 1.28; 95% CI = 1.08-1.52; number of studies = 21; Table 2A) [32], miscarriage (OR = 1.60; 95% CI = 1.11-2.30; number of studies = 6; Table 2A) [29], and small-for-gestational-age infants (OR = 1.43; 95% CI = 1.08-1.91; number of studies = 19; Table 2B) [32]. Vitamin D deficiency also increased the risk of GDM (OR = 1.38; 95% CI = 1.22 -1.57; number of studies = 31) [28], recurrent miscarriage (OR = 4.02; 95% CI = 2.23-7.25; number of studies = 12) [23], and bacterial vaginosis (OR = 1.54; 95% CI = 1.25-1.91; number of studies = 14) (Table 2A) [16]. The highest level of vitamin D had a significant lower risk of preeclampsia compared with the lowest level (RR = 0.68; 95% CI = 0.55-0.85; number of studies = 29; Table 2A) [34].…”
Section: Vitamin D In Pregnancy Related To Health Outcomes In Observa...mentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review [56] of women from Mediterranean countries, including pregnant women, revealed a 23-90% deficiency prevalence with possible adverse consequences for maternal and neonatal health. Low vitamin D levels have been associated with a greater risk for preeclampsia, GDM, and bacterial vaginosis [57][58][59], preterm birth [57,58,60,61], giving birth to small-for-gestational-age (SGA) [58,61] and LBW infants [58], maternal and infant infections [57], the need for caesarian deliveries [57,58], lower offspring scores in mental and developmental tests [61], and many more. Among the risk factors for low vitamin D concentrations are less time spent outdoors, the use of sunscreens, lower skin exposure due to clothing choices, or avoidance of exposure to UVB radiation [54].…”
Section: Nutritional Risk Factors During Pregnancymentioning
confidence: 99%
“…Clinical studies have shown that vitamin D supplementation can lower androgen levels, lower anti-Mullerian hormone (AMH) levels [ 14 , 15 ], normalize the metabolic profile, and regularize periods in women with polycystic ovarian syndrome (PCOS) [ 16 , 17 ]. In fact, low serum 25(OH)D concentrations have been linked to problems of infertility [ 18 , 19 ], endometriosis [ 20 ], polycystic ovary syndrome (PCOS) [ 16 , 17 , 21 , 22 ], as well as adverse pregnancy outcomes, including spontaneous abortions [ 23 ], gestational diabetes [ 24 , 25 ], bacterial vaginosis [ 26 ], preeclampsia [ 27 , 28 ], neonatal hypocalcemia [ 29 ], prematurity, and low birth weight [ 30 ], as well as fetal and infant growth disorders [ 31 ].…”
Section: Introductionmentioning
confidence: 99%